Scepticism and Anti-Scepticism in Medieval Jewish Philosophy and Thought - Haliva, Racheli (Studies and Texts in Scepticism, 2018)
The tension between reason and revelation has occupied Jewish philosophers for centuries, who, on the one hand, were committed to defending Judaism and on the other hand to remaining loyal to philosophical principles. The present publication focuses on sceptical questions, methods, strategies, and approaches raised by Jewish thinkers in the Middle Ages.